PENGARUH PELARUT TERHADAP RENDEMEN MINYAK ATSIRI PALA (The Effect of Solvent On Nutmeg Essetial Oil Yield) - Kaimudin, Marni; Radiena, Mozes (Baristand Industri Banda Aceh, 2016)
Potential nutmeg plant 10.918 ha are scattered in several districts in Maluku and one of themcontained in the Banda Islands, Central Maluku district. With natural potential so great but Small MediumEnterprise (SME) for the oil refinery of the nutmeg seed has not developed rapidly. Refining generally usewater as a solvent because more economically. Beside of the water solvent, solvent distillation process iscarried out with ether, hexane, toluene and methanol with a purpose to see the effect of the solvent on theyield of nutmeg essential oil produced. The method used in this study is refining the system soxhletation.Results of nutmeg oil refining, obtained yield of 10% for solvent ether, 16%, of solvent diethylether, 4.04%for the solvent hexane, 72.04% for the solvent toluene and 85% for the methanol solvent. Oil state testresults which include the color and odor of ether that is light yellow, slightly peculiar smell of nutmeg oil,diethyl ether to light yellow, slightly peculiar smell of nutmeg oil, hexane color to egg yolks, not the typicalsmell of nutmeg oil, for toluene color orange, not the typical smell of nutmeg oil and methanol brick redcolor, the smell is not typical nutmeg oil. As a comparison is refined with solvent water color is clear strawbrass,distinctive smell of nutmeg oil, as contained in nutmeg oil SNI test for this type of situation, namelythe color of colorless to pale yellow and the typical smell of nutmeg oil.